Local road traffic activity and the prevalence, severity, and persistence of wheeze in school children: combined cross sectional and longitudinal study. Issue 3 (1st March 2000) - Venn, Andrea; Lewis, Sarah; Cooper, Marie; Hubbard, Richard; Hill, Ian; Boddy, Rachel; Bell, Margaret; Britton, John
Abstract : OBJECTIVES: To investigate the relation between local road traffic activity and the occurrence, severity, and persistence of wheeze in children. METHODS: Data on wheeze and asthma were collected in a cross sectional questionnaire survey of 22 968 primary school children (age 4–11) and 27 826 secondary school children (age 11–16) in the Nottingham area. Direct measures of road traffic flow were made in the locality of each school and combined with Local Authority traffic data for major roads to estimate local traffic activity in vehicle metres/day/km 2 . Assessment of the effects of potential confounders was performed in nested case-control groups of 6576 primary and 5936 secondary children. Data on frequency of wheeze were collected for the cases to study disease severity. Longitudinal data on a historical cohort of 883 children who reported wheeze when aged 4–11 in 1988 were used to study the persistence of wheeze into adolescence. RESULTS: Unadjusted prevalence of wheeze in the past year within schools varied widely but was not associated with traffic activity in the school locality (weighted regression coefficient β=−0.01, p=0.93 for primary schools, β=−0.18, p=0.26 for secondary schools). The risk of wheeze in individual primary school children was not associated with traffic activity analysed as a continuous variable, although there was some suggestion of a weak, non-linear plateau effect. Similar effects were found for diagnosed asthma and recent cough. There was no evidence of any relation between traffic activity and risk of wheeze in secondary school children. There were positive but non-significant dose related effects of traffic activity on wheeze severity in primary and secondary children and on persistence of wheeze in the longitudinal cohort. CONCLUSIONS: Traffic activity in the school locality is not a major determinant of wheeze in children.